Answer:
The true anomaly q will be such that the q=
where e is the eccentricity of the ellipse.
Step-by-step explanation:
For ellipse velocity components and velocity is given as
![v_r=(\mu)/(h) e \, sin\theta\\v_p=(h)/(r)=(h)/((h^2)/(\mu)(1)/(1+ecos\theta))\\v_(eclipse)=√(v_r^2 +v_p^2)\\v_(eclipse)=\sqrt{((\mu)/(h) e \, sin\theta)^2 +((h)/((h^2)/(\mu)(1)/(1+ecos\theta)))^2}\\\\v_(eclipse)=\sqrt{((\mu)/(h))^2(e^2+1+2ecos\theta)}\\\\v_(eclipse)^2=((\mu)/(h))^2(e^2+1+2ecos\theta)](https://img.qammunity.org/2021/formulas/physics/college/4scbj4te8rv01r282vt16xtk3qjq0ff4xo.png)
For similar radius velocity of circle is given as
![\\v_(circle)^2=(\mu)/(r)\\v_(circle)^2=(\mu)/((h^2)/(\mu)(1)/(1+ecos\theta))\\v_(circle)^2=(\mu^2)/(h^2)(1+ecos\theta)](https://img.qammunity.org/2021/formulas/physics/college/cu31ts7ygpjx4kh2ko1950fhwj7v7yus38.png)
Now as per the condition
![v_(eclipse)^2=v_(circle)^2\\((\mu)/(h))^2(e^2+1+2ecos\theta)=(\mu^2)/(h^2)(1+ecos\theta)\\(e^2+1+2ecos\theta)=(1+ecos\theta)\\ecos\theta=-e^2\\cos\theta=-e\\theta=cos^(-1)(e)](https://img.qammunity.org/2021/formulas/physics/college/borfty3id3872wcrdqmlyq19ltufart25c.png)
So the true anomaly q will be such that the q=
where e is the eccentricity of the ellipse.